Pelaksanaan Eksekusi Hak Asuh Anak Dalam Perkara Perceraian (Studi Kasus Putusan No 1618/Pdt.G/2020/PA.Smp) - Laily Lukita Nilam Sari; Wasis Suprayitno; Kukuh Dwi Kurniawan (Indonesia Law Reform Journal, 2022)
Article 1 of Law no. 1 of 1974 states that "marriage is physically and mentally between a man and a woman as husband and wife to form a happy family and based on the Almighty God". However, many problems in the household result in divorce, which causes various problems. One of the problems that occur as a result of divorce is child custody. One example is case decision number 1618/Pdt.G/2020/PA.Smp. This study aims to determine the basic considerations related to child custody following case decision number 1618/Pdt.G/2020/PA.Smp. In addition, it also aims to determine the obstacles in executing child care (Hadhanah) in the decision of the Sumenep Religious Court Number 1618/Pdt.G/2020/PA.Smp. This research is sociological juridical research using a statute approach and a case approach. Results Based on research and discussion, it is known that the Panel of Judges, in deciding this case, used Article 105 of the Compilation of Islamic Law, namely regarding the maintenance of children who are still not mumayyiz and also used the basis of legal considerations that are theoretically appropriate in terms of the principles that are the main reference in providing in the decision, the rules of Islamic law, as well as the provisions of the applicable laws and regulations.